APLIKASI GAME EDUKASI AYO MENGENAL SHOLAWAT UNTUK ANAK USIA 9 TAHUN BERBASIS ANDROID - Aprih Widayanto; Widayanto, Aprih; Setiawan, Agus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
Abstract - Sholawat is a reading in Arabic spoken by Muslims as a sign of honor and appreciation to the Prophet Muhammad SAW. In this modern era, sholawat needs to be introduced to everyone, especially for children. In this case, it is necessary to implement media development to introduce easy-to-understand and interesting sholawat in order to motivate children to know about sholawat at an early age, especially in today's era, many young children are already using gadgets. At this time, Sholawat has been widely introduced through videos uploaded on social media YouTube. But here the author wants to introduce sholawat through interactive educational game application media and with visuals that are more attractive, simple, easy to use. The author uses research methods, observation, interviews and literature study so that later in making the application more systematic and efficient. The educational game application is packaged in a more modern way by following current technological developments, making it faster to be recognized by all users of this educational game application Keywords: Sholawat, Applications, Educational Games